Computation of stretching disks fluid flow of hybrid nanofluid under the effect of variable magnetic field - Zada, Jan; Khan, Aamir; Farooq, Muhammad; Alsubaie, Abdullah Saad; Rezapour, Shahram; İnç, Mustafa (Wiley-V C H Verlag Gmbh, 2025)
Our investigation revolves around probing into the entropy generation and heat transfer phenomena within the context of an unsteady flow of variable magnetic hybrid nanofluid confined between parallel disks. This incorporation of carbon nanotubes (both single-walled and multi-walled) as nano-particles dispersed within a blend of water and ethylene glycol (50%W + 50% EG). To gain a comprehensive understanding of the physical behavior exhibited by hybrid nanofluids, we have introduced innovative models tailored explicitly for this fluid classification. This research also investigates a swirling flow generated by the rotational movement of circular disks along the z-direction. Employing the Buongiorno model, specifically a two-phase nanofluid model, allows for a detailed examination of the thermal behavior of nanoparticles. This analysis highlights the impact of Brownian diffusion and thermophoresis on temperature and concentration distributions within the system. The numerical outcomes and results derived from this analysis have been computed through the HAM and for accuracy is compared with bvp4c program, providing valuable insights into the thermal behavior and distinctive characteristics of these hybrid nanofluids. The novelty of this work has never been shared or compared with any other method. Hybrid nanofluid as Ethylene Glycol cum water transferring heat and mass in SWCNT and MWCNT respectively observed.
Keywords: Group Preserving Scheme; Convection Mhd Flow; Squeezing Flow; Thermal-Radiation; Base Fluid; Cooling Technology; Boundary-Layer; Heat-Transfer; Nanoparticles; Al2O3